Targeting Mediators of Smoking Persistence with Intranasal Insulin - Hamidovic, Ajna (Frontiers in Pharmacology, 2017)
Rapid-acting, non-irritating nasal treatment options for smoking cessation pharmacotherapy are lacking. The halt in development is due, in part, to a difficulty in delivering compounds across the blood brain barrier. Recently, in both human and animal models, insulin was shown to be capable of being transported to the cerebrospinal fluid and various brain regions via the “nose-to-brain” pathway, which bypasses the blood brain barrier, but is not free of its own unique, though different from blood brain barrier, challenges. This review will first evaluate and critique pharmacokinetic and pharmacodynamics evidence of intranasal insulin (i.e. nose-to-brain) delivery. As intranasal insulin has been shown in clinical trials to be effective in reducing nicotine cravings, in the remainder of the review, hypothesis-generating literature for additional mediators (i.e. other than the already shown nicotine craving) of smoking persistence will be reviewed. In particular, weight gain, impulsive behavior and anhedonia have been shown to contribute to the inability to quit. For each of these, after reviewing how the mediator promotes smoking, intranasal insulin literature from animal and clinical models will be critiqued in assessing whether a hypothesis may be generated that intranasal insulin may alleviate it, thereby potentially contributing to a successful smoking cessation outcome.